Trapped in a maze: how social control institutions drive family poverty and inequality - Paik, Leslie (University of California Press, 2021)
Prologue : the Hernandez family -- Introduction -- Concurrent involvement : challenges in navigating multiple institutions at once -- Revisiting the past to understand the present : temporal view of family multi-institutional involvement -- Who's in the family? multi-household exploration of the maze -- Mitigating factors : institutional mismatch and unpredictability in the maze -- Conclusion : reflections on the maze and practical steps forward -- Postscript : Brief update about the families -- Appendix A : Methodology and reflexivity -- Appendix B : List of families.